Pengaruh Kesiapan Guru dalam Implementasi Kurikulum Merdeka terhadap Minat Belajar dan Motivasi Belajar Peserta Didik pada Pembelajaran Pendidikan Agama Islam Tingkat SMP - Ahadiyaah, Tyas Lailatul; Ikhrom, Ikhrom; Darmuin, Darmuin (YASIN, 2025)
This investigation examines how teacher preparedness in implementing the independent curriculum impacts student engagement and motivation in Islamic religious education at the junior high level. The primary objective of this paper is to determine the effect of teacher preparedness (designated as X) regarding the implementation of the independent curriculum on students' interest in learning (Y1) and its effect on their learning motivation (Y2), specifically within the context of Islamic religious education for junior high students. Employing a quantitative methodological framework, this research utilized simple regression analysis for hypothesis testing. A simple random sampling technique was applied to select the participants, comprising 95 teachers and 95 students drawn from the overall population. Data were collected through questionnaires. The outcomes of the study indicate the following: 1) With a calculated t-value of 3.195 exceeding the critical value of 1.665 (t_count = 3.195 ≥ t_table = 1.665), the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. This signifies that teacher preparedness exerts an influence on students' interest in studying Islamic religious education (PAI). Furthermore, the R-squared value (R²) is 0.315, or 31.5%, suggesting that enhanced teacher readiness correlates with greater student interest in learning, and vice versa. 2) The computed t-value is 4.319, which is also greater than the critical value of 1.665 (t_count = 4.319 ≥ t_table = 1.665). Consequently, H₀ is rejected, and H₁ is accepted, indicating an influence of teacher preparedness on learning motivation. The R-squared value (R²) in this case is 0.409, or 40.9%. This leads to the conclusion that higher levels of teacher readiness are associated with increased student learning motivation. Therefore, fostering student interest and motivation in learning necessitates both adequate preparation for educators and active involvement from parents, with the expectation that this will enable students to cultivate their interests beneficially for their school, families, and community.